Inhibition of oxytocin and vasopressin neuron activity in rat hypothalamic paraventricular nucleus by relaxin‐3–RXFP3 signalling. (27th February 2017) - Kania, Alan; Gugula, Anna; Grabowiecka, Agnieszka; de Ávila, Camila; Blasiak, Tomasz; Rajfur, Zenon; Lewandowski, Marian H.; Hess, Grzegorz; Timofeeva, Elena; Gundlach, Andrew L.; Blasiak, Anna
Abstract : Key points: Relaxin‐3 is a stress‐responsive neuropeptide that acts at its cognate receptor, RXFP3, to alter behaviours including feeding. In this study, we have demonstrated a direct, RXFP3‐dependent, inhibitory action of relaxin‐3 on oxytocin and vasopressin paraventricular nucleus (PVN) neuron electrical activity, a putative cellular mechanism of orexigenic actions of relaxin‐3. We observed a Gαi/o ‐protein‐dependent inhibitory influence of selective RXFP3 activation on PVN neuronal activity in vitro and demonstrated a direct action of RXFP3 activation on oxytocin and vasopressin PVN neurons, confirmed by their abundant expression of RXFP3 mRNA. Moreover, we demonstrated that RXFP3 activation induces a cadmium‐sensitive outward current, which indicates the involvement of a characteristic magnocellular neuron outward potassium current. Furthermore, we identified an abundance of relaxin‐3‐immunoreactive axons/fibres originating from the nucleus incertus in close proximity to the PVN, but associated with sparse relaxin‐3‐containing fibres/terminals within the PVN. Abstract: The paraventricular nucleus of the hypothalamus (PVN) plays an essential role in the control of food intake and energy expenditure by integrating multiple neural and humoral inputs. Recent studies have demonstrated that intracerebroventricular and intra‐PVN injections of the neuropeptide relaxin‐3 or selective relaxin‐3 receptor (RXFP3) agonists produce robust feeding in satiated rats, but the cellular and molecular mechanisms of action associated with these orexigenic effects have not been identified. In the present studies, using rat brain slices, we demonstrated that relaxin‐3, acting through its cognate G‐protein‐coupled receptor, RXFP3, hyperpolarized a majority of putative magnocellular PVN neurons (88%, 22/25), including cells producing the anorexigenic neuropeptides, oxytocin and vasopressin. Importantly, the action of relaxin‐3 persisted in the presence of tetrodotoxin and glutamate/GABA receptor antagonists, indicating its direct action on PVN neurons. Similar inhibitory effects on PVN oxytocin and vasopressin neurons were produced by the RXFP3 agonist, RXFP3‐A2 (82%, 80/98 cells). In situ hybridization histochemistry revealed a strong colocalization of RXFP3 mRNA with oxytocin and vasopressin immunoreactivity in rat PVN neurons. A smaller percentage of putative parvocellular PVN neurons was sensitive to RXFP3‐A2 (40%, 16/40 cells). These data, along with a demonstration of abundant peri‐PVN and sparse intra‐PVN relaxin‐3‐immunoreactive nerve fibres, originating from the nucleus incertus, the major source of relaxin‐3 neurons, identify a strong inhibitory influence of relaxin‐3–RXFP3 signalling on the electrical activity of PVN oxytocin and vasopressin neurons, consistent with the orexigenic effect of RXFP3 activation observed in vivo . Key points: Relaxin‐3 is a stress‐responsive neuropeptide that acts at its cognate receptor, RXFP3, to alter behaviours including feeding. In this study, we have demonstrated a direct, RXFP3‐dependent, inhibitory action of relaxin‐3 on oxytocin and vasopressin paraventricular nucleus (PVN) neuron electrical activity, a putative cellular mechanism of orexigenic actions of relaxin‐3. We observed a Gαi/o ‐protein‐dependent inhibitory influence of selective RXFP3 activation on PVN neuronal activity in vitro and demonstrated a direct action of RXFP3 activation on oxytocin and vasopressin PVN neurons, confirmed by their abundant expression of RXFP3 mRNA. Moreover, we demonstrated that RXFP3 activation induces a cadmium‐sensitive outward current, which indicates the involvement of a characteristic magnocellular neuron outward potassium current. Furthermore, we identified an abundance of relaxin‐3‐immunoreactive axons/fibres originating from the nucleus incertus in close proximity to the PVN, but associated with sparse relaxin‐3‐containing fibres/terminals within the PVN.